Self-Regulation of the Communicational field in the Voting Process: A Legal-Political Response to the Problem of Electoral Neutrality practiced through Social Networks.: An analysis of the Colombian Case and its Impact on Latin America (Law, State and Telecommunications Review, 2018)
Purpose ”“ The main proposal of this scientific article is to find some of the shortcomings that may arise from the influence of social networks on the voting decision of Colombian citizens, by reason of the logic of their own democratic system, as well as try to find contributions of the responsive theory to strengthen these fallings. Methodology/approach/design ”“ To achieve the objective of the research, it is proposed a logical-deductive methodology with a qualitative approach. The main theories on which the research will be based are the systems theory, deliberative theory and responsive theory. The empirical support used is the case studies tool.Findings ”“ Among the main results obtained with the research are the analysis of the influence of political candidates on the flow of information in social networks. It is recommended that Colombia strengthen its electoral regulatory system. Practical implications ”“ The main practical contributions of this research are at the political-legal level, since this seeks to strengthen deliberative processes in social networks, and to generate critical awareness and political identity and voting.Originality/value ”“ This research is original since it analyzes the problem of the influence of the media from another aspect not yet explored sufficiently, from the perspective of the influence of social networks on the decision of citizens to vote, which is why it has a high political and legal value, since it seeks to strengthen the constitutional and democratic order.